Early postoperative mortality after surgery for rectal cancer in Sweden, 2000–2011. (June 2014) - Rutegård, M.; Haapamäki, M.; Matthiessen, P.; Rutegård, J.
Abstract Aim Postoperative mortality has traditionally been defined as death within 30 days of surgery. Such mortality after rectal cancer resection has declined significantly during the last decades. However, it is possible that this decline can be explained merely by a shift towards an increase in 90‐day mortality. Method A nationwide cohort study was based on data from the Swedish Colorectal Cancer Registry and the Swedish Patient Registry concerning patients who had undergone surgical resection for rectal cancer in 2000–2011. Unconditional logistic regression was used to calculate ORs with 95% CIs regarding mortality in different calendar periods (2000–2003, 2004–2007 and 2008–2011) in two different postoperative time periods (0–30 days and 31–90 days). Results Some 15 437 patients were included in this surgical cohort. Mortality within 30 days of surgery decreased from 2.1% in 2000–2003 to 1.6% in 2008–2011, whilst the corresponding mortality within the 31‐ to 90‐day time window decreased from 2.1% to 1.4%. The adjusted risk of 30‐day mortality in 2008–2011 was statistically significantly decreased compared with that in 2000–2003 (OR = 0.67; 95% CI: 0.48–0.93) and mortality in the 31‐ to 90‐day time window was also reduced for 2008–2011 compared with 2000–2003 (OR = 0.71; 95% CI: 0.51–0.99). Conclusion This population‐based, nationwide Swedish study indicates that postoperative mortality, as measured within 30 days and 31–90 days after surgery, has decreased with time. However, no relevant shift from earlier to later postoperative mortality was discerned.